Effect of 6-Axis Robot Speed on Cycle Time and Accuracy as Pick and Place Media on Dummy CNC - Jayasri Iniko Wirefa; Risfendra (Department of Electrical Engineering Universitas Negeri Padang, 2025)
This study investigates the impact of a 6-axis robot's speed on cycle time and accuracy in pick-and-place operations integrated with CNC machines. As Industry 4.0 emphasizes automation and efficiency, optimizing robotic performance in manufacturing processes is critical. The experiment tested five speed variations (20%, 40%, 60%, 80%, and 100%) to analyze their effects on cycle time and placement accuracy. Results demonstrated a significant reduction in cycle time as speed increased: from an average of 66.45 seconds at 20% speed to 26.83 seconds at 100%. However, maximum speed (100%) introduced vibrations, causing placement errors and robot failures due to excessive force detection. In contrast, 80% speed achieved an optimal balance, maintaining high accuracy (no errors) with a cycle time of 29.07 second, only 2.24 seconds slower than 100%. The study concludes that while higher speeds enhance productivity, 80% is recommended as the default setting to ensure precision and operational reliability. The integration of sensors, grippers, and automated door control further validated the system's effectiveness in industrial CNC applications.